An open-label, randomized trial indicates that everolimus with tacrolimus or cyclosporine is comparable to standard immunosuppression in de novo kidney transplant patients - Sommerer, Claudia; Suwelack, Barbara; Dragun, Duska; Schenker, Peter (Kidney international, 2019)
This is a randomized trial (ATHENA study) in de novo kidney transplant patients to compare everolimus versus mycophenolic acid (MPA) with similar tacrolimus exposure in both groups, or everolimus with concomitant tacrolimus or cyclosporine (CsA), in an unselected population. In this 12-month, multicenter, open-label study, de novo kidney transplant recipients were randomized to everolimus with tacrolimus (EVR/TAC), everolimus with CsA (EVR/CsA) or MPA with tacrolimus (MPA/TAC), with similar tacrolimus exposure in both groups. Non-inferiority of the primary end point (estimated glomerular filtration rate [eGFR] at month 12), assessed in the per-protocol population of 338 patients, was not shown for EVR/TAC or EVR/CsA versus MPA/TAC. In 123 patients with TAC levels within the protocol-specified range, eGFR outcomes were comparable between groups. The mean increase in eGFR during months 1 to 12 post-transplant, analyzed post hoc, was similar with EVR/TAC or EVR/CsA versus MPA/TAC. The incidence of treatment failure (biopsy proven acute rejection, graft loss or death) was not significant for EVR/TAC but significant for EVR/CsA versus MPA/TAC. Most biopsy-proven acute rejection events in this study were graded mild (BANFF IA). There were no differences in proteinuria between groups. Cytomegalovirus and BK virus infection were significantly more frequent with MPA/TAC. Thus, everolimus with TAC or CsA showed comparable efficacy to MPA/TAC in de novo kidney transplant patients. Non-inferiority of renal function, when pre-specified, was not shown, but the mean increase in eGFR from month 1 to 12 was comparable to MPA/TAC.